The right to fight : a history of African Americans in the military - Astor, Gerald, 1926-2007. (Novato, CA : Presidio, 1998)
Describes the role of African Americans in the military from the Boston Massacre to the present day.
1. The Long Voyage -- 2. The Struggle Begins -- 3. The Civil War -- 4. The Buffalo Soldiers -- 5. The War with Spain -- 6. New Beginnings and Brownsville, Texas -- 7. Navy White, Pancho Villa, and Houston -- 8. World War I -- 9. Between the Wars -- 10. The Coming of World War II -- 11. Command and Control -- 12. Soldiers, Airmen, Sailors, and Marines -- 13. Combat and Other Battles -- 14. Forward Movement and Reversals -- 15. The End of the War and Return to the Past -- 16. Postmortems and Pullbacks -- 17. The Walls Begin to Tumble -- 18. Korea -- 19. Integration Begins -- 20. Policy and People -- 21. Vietnam -- 22. Rough Seas, Turbulent Air -- 23. Shifting Sands, Settling Down -- 24. After-Action Critique.
Includes bibliographical references (pages 518-520) and index.
Keywords: Race discrimination -- United States -- History; Armed Forces -- African Americans